TO DETERMINE THE LEVELS OF GOOD CHOLESTEROL-HDL IN THE PATIENTS HAVING ISCHEMIC STROKE AND DISEASE OUTCOME IN NEXT 2 WEEKS - AHMED , M; AROOJ , T; SEHAR, R; SADIQ, Y; SHABBIR , H; BAIG , ZL (Biological and Clinical Sciences Research Journal, 2023)
To know about the levels of good cholesterol-HDL in ischemic stroke patients and disease outcomes in the next 2 weeks. This study was carried out from July 2021 to Jan 2022 at the Department of Medicine Divisional Teaching Hospital Mir Pur Azad Jammu and Kashmir. Inclusion criteria were any patient aged between > 20 years old, both males and females admitted with sudden onset of focal neurological deficit. They diagnosed the CT brain as an ischemic stroke less than 24 hours old.HDL-C levels immediately after admission before starting aspirin and statins. The patient’s functional outcome was assessed by using the ADL scale at 2 weeks. The data collected was evaluated on SPSS. A total of 150 patients were included in the study. The mean age of patients was 60.16 + 1.35 years. There were 85 (68%) males and 40 (32%) females. One hundred-five patients (84%) had serum HDL-C levels less than the appropriate range, and 20 (16%) had serum HDL-C levels within the appropriate range. Patients with high HDL-C levels show statistically significant better functional outcomes (p-value 0.001). We conclude that high serum HDL-C levels are strongly associated with better functional outcomes 2 weeks after stroke, and patients with high HDL-C levels are at reduced risk of developing stroke.